Pengaruh Suhu dan Lama Penyimpanan Air Isi Ulang terhadap Kualitas Air Minum: (Studi Kasus di Depot Air Minum, Kota Kendari, Provinsi Sulawesi Tenggara) - Alwan, Fahril; Rosdiana, Rosdiana; Ndibale, Wa (Universitas Muhammadiyah Kendari, 2025)
Refillable drinking water is a source of drinking water widely used by the public, especially in urban areas, because it is more affordable than bottled water. However, the quality of refillable drinking water is often a concern, because it can be affected by various factors, such as the quality of the water source, the processing process, and storage and distribution methods. This study aims to examine the effect of temperature and storage duration on drinking water quality in refillable water. Good drinking water quality is very important for health, but is often affected by improper storage factors. This study used an experimental approach with variations in indoor and outdoor storage temperatures and storage durations (1, 3, and 6 days). Refill water samples were taken from a refill drinking water depot in the BTN area. Aldzaky Residence, Anduonohu ​​Village, Poasia District, Kendari City, Southeast Sulawesi Province, then tested for quality based on physical, chemical, and microbiological parameters, including pH, odor, taste and color, E-coli bacteria content and iron metal content. The results showed that storage temperature and storage time significantly influenced drinking water quality. The higher the storage temperature and the longer the storage time, the water quality tended to decline, especially in bacteriological parameters and heavy metal content. This decline in quality has the potential to harm consumer health if not stored properly. Based on these findings, it is recommended that refill water be stored at a lower temperature and consumed within a short time to maintain its quality.